(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation of alcohol use among students of Lam Dong Medical College and Da Lat College, 2024; and analyze a number of factors related to the current state of alcohol use by research subjects. Research subjects and methods: Cross-sectional descriptive study on 306 students from January to June 2024 (66 students at Lam Dong Medical College, 240 students at Da Lat College). The quantitative data collection tool is a set of pre-written structured questions, built on the AUDIT scale, a scale approved and introduced by the World Health Organization. Results: The average age of the study subjects was 20.6 ± 3.4 years old, with the main proportion of female students (77.8%). The rate of students using alcohol at harmful levels is 28.5%. The likelihood of harmful alcohol use is higher among students whose family members use alcohol with OR = 3.0; 95%CI = 2.0-6.0; the relationship is statistically significant with p < 0.05. There was no relationship between general characteristics and factors of friends using alcohol and the rate of harmful alcohol use of the study subjects (p > 0.05). Conclusion: The rate of alcohol use among male students is still high. Family factors with alcohol users are related to students’ alcohol use.